Forum: The Holocaust in Virtual Reality: Ethics and Possibilities. Issue 2 (3rd July 2022) - Rich, Jennifer; Dack, Mikkel
ABSTRACT: This article addresses the fraught relationship between technology and representations of the Holocaust by examining the ethical dilemmas and opportunistic possibilities of a developing virtual reality tool for teaching and learning. Its focus is a pilot project at Rowan University in New Jersey, entitled the Warsaw Project, which seeks to balance the immersive nature of virtual and augmented realities with best practices, robust student engagement, and historical accuracy. In this article, we illustrate the project origins, scope, and content and share some of the major ethical dilemmas encountered as well as unexpected outcomes. Ultimately, we argue that advanced digital platforms and immersive technologies can, within an appropriate learning environment and when guided by qualified instruction, serve as an effective pedagogical tool and inform students in a way otherwise unachievable through literature and film.